The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.5005/jp-journals-10024-2316
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Cervical Vertebrae Volume Parameter and the Skeletal Maturation Status

Abstract: Measurement of volumes of the 4th CVVP could be used as simple quantitative analysis in clinical practice to evaluate the maturity in orthodontic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 106 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…The 27 moderate and high-quality articles were categorized by topics as follows: 16 articles compared the CVM method with the HWM, 2,5,9,[13][14][15][16]19,21,[25][26][27][28][29][30]32 2 articles compared the CVM method with chronologic age, 39,40 1 article compared the CVM method with MP3, 42 3 articles [46][47][48] compared the CVM method with dental age, 3 articles compared the CVM method with body height, 43,44,49 1 article compared the CVM method with both chronologic age and dental age, 37 and finally 1 article compared the CVM method with both HWM and MP3. 24…”
Section: Resultsmentioning
confidence: 99%
“…The 27 moderate and high-quality articles were categorized by topics as follows: 16 articles compared the CVM method with the HWM, 2,5,9,[13][14][15][16]19,21,[25][26][27][28][29][30]32 2 articles compared the CVM method with chronologic age, 39,40 1 article compared the CVM method with MP3, 42 3 articles [46][47][48] compared the CVM method with dental age, 3 articles compared the CVM method with body height, 43,44,49 1 article compared the CVM method with both chronologic age and dental age, 37 and finally 1 article compared the CVM method with both HWM and MP3. 24…”
Section: Resultsmentioning
confidence: 99%
“…There is an existing association present between craniofacial and cranio-cervical morphology according to literature. 2,3,7 A previous study has concluded that there is a co relation between the skeletal maturation age and the volume of bodies of second, third, and fourth cervical vertebrae. In a study by Ousama et al in 2018, it was seen that there was a moderate to strong positive co-relation between the cervical vertebral volume parameter and the MP3 stages, specifically of the fourth cervical vertebrae.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ousama et al in 2018, it was seen that there was a moderate to strong positive co-relation between the cervical vertebral volume parameter and the MP3 stages, specifically of the fourth cervical vertebrae. 7 Volumetric analysis was done to ascertain if there was any relation between the body volume of cervical vertebrae and different malocclusions. This study was done to evaluate and compare the vertebral body volume of second, third, and fourth cervical vertebrae in different classes of malocclusion with varying growth patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous literature included Chen’s suggestion of a quantitative cervical vertebral method to assess skeletal maturation of Chinese adolescence[ 12 ] and Mito’s offer of a quantitative cervical vertebral BA (CVBA) formula for Japanese girls. [ 11 ] Moreover, Ayach and Hadad[ 16 ] presented a quantitative method to measure the volume of the fourth cervical vertebra on CBCT radiograph of Syrian adolescence. Because of difference in racial morphology, it is necessary to propose a quantitative method for assessing skeletal maturation in Vietnamese subjects based on the morphology of their cervical vertebrae.…”
Section: Introductionmentioning
confidence: 99%